The Environment of the Period - The Subject of the Work (In Terms of His Life and Lyrics) - Samatova Ismigul (Global Scientific Publishing, 2023)
Muhammad Aminkhoja Muqimi is an Uzbek writer, poet, satirist. One of the founders of Uzbek realism. This article analyzes the poet's life path and images of socio-economic life in his works. The socio-economic aspects of the events that happened in the life of the population at the end of the 19th century and the beginning of the 20th century are covered in detail. Mukimi used the events he witnessed as the main theme of his works, described the events truthfully, and ruthlessly exposed the officials. The poet's nickname "Mukimi" means "permanence". True study of such works, our heritage, their scientific analysis is one of the urgent tasks of our day.
Keywords: Muqimi; Muqimi's works; Hajvi Bekturdiy